1994
DOI: 10.1159/000246816
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Eosinophilic Pustular Folliculitis

Abstract: Background: Eosinophilic pustular folliculitis (EPF) is a cutaneous inflammatory follicular disorder of unknown etiology. The diagnosis is established on the basis of clinical and histopathologic features. In only a few instances has EPF been described in children. Objective and Methods: We describe the clinical and histopathologic features of a recurrent follicular eosinophilic pustular eruption involving the scalp in 2 children. Previously reported cases of EPF in childhood below 14 years of age are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Twelve of the previously published cases were excluded, 13,20-27 some of which had already been questioned by other authors 28 : 1 atypical case on both clinical and histologic grounds (genital location exclusively, dermal infiltrate rich in neutrophils in 1 biopsy specimen, and in lymphocytes and macrophages in another) 25 ; 3 cases associated with immunodeficiency 26,27 ; 1 patient who developed sepsis with hepatic and pulmonary involvement in whom immunodeficiency was not ruled out 13 ; and 1 exceptional case in which the eruption did not recur, the histologic findings were inconclusive, and that was treated with granulocyte-colony stimulating factor (G-CSF) because of the extraordinarily high eosinophilia. 22 There were 6 more cases that were also excluded because of their atypical manifestations: a 4-year-old child who had recurrent vesicles and pustules along with erythema multiformeelike lesions on the abdomen and lower limbs that might have corresponded to arthropod bites 23 ; an 8-yearold boy with mucosal involvement, mixed dermal inflammatory infiltrate with eosinophils and neutrophils, and good response to dapsone in whom linear IgA was not excluded 20 ; an 11-year-old girl who presented with an isolated annular plaque on the cheek showing a dense eosinophilic infiltrate and necrotizing vasculitis of the small vessels, 24 which is not a feature of EPFI; a 5-year-old girl with ulcerated lesions on the lower legs that resolved in 2 weeks 21 ; and 2 more patients who presented with crops of pustular lesions on the trunk and lower limbs for 3 months' duration who demonstrated hypersensitivity to Dermatophagoides pteronyssinus and elevated IgE levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Twelve of the previously published cases were excluded, 13,20-27 some of which had already been questioned by other authors 28 : 1 atypical case on both clinical and histologic grounds (genital location exclusively, dermal infiltrate rich in neutrophils in 1 biopsy specimen, and in lymphocytes and macrophages in another) 25 ; 3 cases associated with immunodeficiency 26,27 ; 1 patient who developed sepsis with hepatic and pulmonary involvement in whom immunodeficiency was not ruled out 13 ; and 1 exceptional case in which the eruption did not recur, the histologic findings were inconclusive, and that was treated with granulocyte-colony stimulating factor (G-CSF) because of the extraordinarily high eosinophilia. 22 There were 6 more cases that were also excluded because of their atypical manifestations: a 4-year-old child who had recurrent vesicles and pustules along with erythema multiformeelike lesions on the abdomen and lower limbs that might have corresponded to arthropod bites 23 ; an 8-yearold boy with mucosal involvement, mixed dermal inflammatory infiltrate with eosinophils and neutrophils, and good response to dapsone in whom linear IgA was not excluded 20 ; an 11-year-old girl who presented with an isolated annular plaque on the cheek showing a dense eosinophilic infiltrate and necrotizing vasculitis of the small vessels, 24 which is not a feature of EPFI; a 5-year-old girl with ulcerated lesions on the lower legs that resolved in 2 weeks 21 ; and 2 more patients who presented with crops of pustular lesions on the trunk and lower limbs for 3 months' duration who demonstrated hypersensitivity to Dermatophagoides pteronyssinus and elevated IgE levels.…”
Section: Resultsmentioning
confidence: 99%
“…These were isolated cases, 3,5,7 whereas many patients were treated ineffectively with antibiotics before being given the diagnosis. [2][3][4][5][6][7][8][9]11,12,14,15,17,19 The good response could be considered as coincidental, because the process tends to be self-limiting, even without treatment, 15,18 but some authors favor the antichemotactic activity of some antibiotics such as erythromycin. 7 Cetirizine has also been successfully used by some authors, who advocate its antieosinophilic activity and antipruritic effect, 3 as has cimetidine.…”
Section: Resultsmentioning
confidence: 99%
“…The data were examined with regards to the epidemiology (age, sex, ethnic group), clinical characteristics (area of involvement, morphology and laboratory investigations) and treatment outcome. Cases of HIV-associated eosinophilic folliculitis 6 and paediatric EPF 7,8 were excluded, as these entities are clinically distinct from classic EPF.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, there may be some overlap in pustular diseases of infancy, 12 particularly infantile eosinophilic pustular folliculitis and IA, as suggested by several authors. [13][14][15] The coexistence of atopic dermatitis and elevated serum IgE was noted in earlier reports of IA. 15 Although Dromy et al 6 attributed this observation to coincidence, Mancini et al 8 reported that 5 of 21 patients with IA had coexisting atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%